Definition of a core collection for cassava - Hershey, Clair H.; Iglesias, C.A.; Iwanaga, Masaru; Tohme, Joseph M. (International Plant Genetic Resources Institute, 1994)
The main responsibility of CIAT as a curator of the world`s cassava germplasm is to assure long-term conservation at low risk of genetic loss and to facilitate access to genetic variability. The present collection of 5477 accessions is maintained both in the field and in vitro at CIAT headquarters in Cali, Colombia. For purposes of improving the efficiency and effectiveness of collecting, conservation and evaluation, a core collection of 630 accessions has been selected to represent the total diversity of the species. The theoretical basis of core collections is discussed and procedures for the definition of a cassava core collection are presented. Short-, medium- and long-term implications of this strategy for global germplasm management are reviewed